2011
DOI: 10.1111/j.1439-0272.2011.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Bovine serum albumin: survival and osmolarity effect in bovine spermatozoa stored above freezing point

Abstract: Liquid nitrogen preservation in remote farms is a limitation. The goal of this study was to determine optimum temperature above freezing point for bovine spermatozoa preservation using bovine serum albumin (BSA) as a supplementation. Pooled semen sample from three ejaculates was subjected to various BSA concentration (1, 4, 8 and 12 mg ml(-1)), before incubation in different above freezing point temperatures (4, 25 and 37 °C). Viability assessment was carried out against time from day 0 (fresh sample) until al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…This observation is not surprising considering the numerous benefits BSA provides to the in vitro embryo culture (reviewed in [31]), including its antioxidant, nutritive and pH buffer roles during embryonic development. Additionally, other studies have also reported the benefits of BSA prolonging viability of sperm stored above the freezing point [32] and protecting sperm DNA [33] and membrane integrity [34]. However, we must note that a proportion of the stored morulae, although small, hatched at 72 h of storage in the NCSU-BSA medium, and these embryos should therefore be discharged for sanitary reasons in commercial ET programs.…”
Section: Discussionmentioning
confidence: 93%
“…This observation is not surprising considering the numerous benefits BSA provides to the in vitro embryo culture (reviewed in [31]), including its antioxidant, nutritive and pH buffer roles during embryonic development. Additionally, other studies have also reported the benefits of BSA prolonging viability of sperm stored above the freezing point [32] and protecting sperm DNA [33] and membrane integrity [34]. However, we must note that a proportion of the stored morulae, although small, hatched at 72 h of storage in the NCSU-BSA medium, and these embryos should therefore be discharged for sanitary reasons in commercial ET programs.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the two most abundant identified proteins in pregnant vs. cyclic ipsilateral ampulla and isthmus, serum albumin has been previously observed as one of the most abundant proteins in OF [26], despite not being expressed by oviduct epithelia [18] or by BOECs [27]. Serum albumin may aid fertilization and early embryo development by regulating OF osmolarity [28]; a physicochemical property to which gametes and embryos are sensitive [28,29]. Furthermore, in vitro studies have…”
Section: Discussionmentioning
confidence: 99%
“…We decided to use storage temperatures of 17 °C and 20 °C in an attempt to decrease the metabolism of the embryos while preserving their viability and thereby ensuring they would remain unhatched until the end of the storage period. We supplemented the storage medium with FCS or BSA at concentration much higher than routine, because of their beneficial effects on cold tolerance in bovine embryos 9,24,30 . This protective role of either of these components could be of particular importance for porcine embryos because they are extremely sensitive to temperatures below 18 °C 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these supplements are also included in cryopreservation media. BSA protects the cell membranes of both embryos 21 and spermatozoa 22–24 during cryopreservation, and increases survival and development rates of porcine embryos when stored in a liquid state 6 . In those studies, survival and hatching rates of embryos stored at 37 °C (morulae) or 25 °C (blastocysts) in medium supplemented with PVA were substantially lower than those obtained using the same medium supplemented with 0.4% BSA.…”
Section: Introductionmentioning
confidence: 99%